Legal Mechanisms for Social Reintegration: An Analysis of Rehabilitation Laws Aimed at Transforming Drug Addicts into Productive Citizens - Wredha Danang Widoyoko; Siti Ngaisah; Ismail Ismail; Diah Ayu Rahmawati; Haryono Haryono (West Science Interdisciplinary Studies, 2024)
This study examines the legal mechanisms for the social reintegration of drug addicts, focusing on rehabilitation as a transformative approach to enabling individuals to re-enter society as productive citizens. Using a normative juridical analysis, the research explores the alignment of national legal frameworks with international human rights standards and evaluates the challenges in implementing rehabilitation-focused policies. Findings reveal that while laws and policies supporting rehabilitation exist, their effectiveness is hindered by societal stigma, inconsistent application, and resource limitations. The study emphasizes the need for policy alignment with international standards, expansion of community-based programs, public awareness campaigns, and strengthened monitoring systems. These measures are essential for creating a supportive legal and social environment conducive to the successful reintegration of drug addicts into society.